Analysis of Intercultural Education Policies in Italy and Spain: A Comparative Perspective - Mario León Sánchez; Massimiliano Fiorucci; Marco Catarci; José González Monteagudo (LED Edizioni Universitarie, 2023)
This article focuses on the evolution of intercultural education in the educational policies of Italy and Spain. The evolution of school regulations and educational practices in both countries presents similar characteristics, including the shift from the paradigm of integration to that of inclusion of students with migrant backgrounds. At the same time, historical and political differences between the two countries have led to the implementation of very different practices, which it is interesting to compare, with a particular interest in those processes of hidden exclusion that are still present in the two educational systems, despite the progress of official regulations. We will present the critical points and strengths of both countries' systems, identifying, on the one hand, the inclusion factors (development of inclusive practices, development of resources and programmes for foreign students) and, on the other hand, the exclusion practices that persist despite legislation (school segregation and school concentration). In the conclusions, we will suggest possible strategies to contribute to the development of intra-European measures and policies to foster the reception of people with a migrant background in national school systems.